Bis(dipyridophenazine)(2‐(2′‐pyridyl)pyrimidine‐4‐carboxylic acid)ruthenium(II) Hexafluorophosphate: A Lesson in Stubbornness. Issue 7 (3rd March 2014) - Joshi, Tanmaya; Pierroz, Vanessa; Ferrari, Stefano; Gasser, Gilles
Abstract Ruthenium complexes are currently considered to be among the most promising alternatives to platinum anticancer drugs. In this work, thirteen structural analogues and organelle/receptor‐targeting peptide bioconjugates of a cytotoxic bis(dppz)‐RuII complex [Ru(dppz)2(CppH)](PF6)2 (1) were prepared, characterized, and assessed for their cytotoxicity and cellular localization (CppH=2‐(2′‐pyridyl)pyrimidine‐4‐carboxylic acid; dppz=dipyrido[3, 2‐a:2′, 3′‐c]phenazine). It was observed that structural modifications (lipophilicity, charge, and size‐based) result in the cytotoxic potency of 1 being compromised. Confocal microscopy studies revealed that unlike 1, the screened complexes/bioconjugates do not have a preferential accumulation in mitochondria. The results of this important structure–activity relationship strongly support our initial hypothesis that accumulation in mitochondria is crucial for 1 to exert its cytotoxic action.